Some salt on your rice? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A weed killer based on cooking salt has been developed by paddy farmers in northern Thailand, with a mixture of 60g NaCl per litre of water). Research workers have confirmed that this is indeed an effective treatment which prevents growth of the...